The Use of Alpha Brainwave to Develop Emphaty Awareness of Vocational School Teachers in Managing Classroom Activities - Gaffar, Muhammad Andriana; Hamdani, Hamdani (Journal of Architectural Research and Education, 2021)
This study aims to explore the benefits of Alpha brainwaves in developing teacher empathy awareness when managing classroom activities on vocational school. The reason for the research being conducted is the fact that most of the teachers are still struggling and find it difficult to deal with students' misbehavior in the classroom because it has an impact on the overall class activities. One of the competencies that every teacher must have is social competence, namely the ability to manage social relations which requires various skills, abilities and capacities in solving problems that occur in interpersonal relationships. The significance of social competence for teachers can be felt in many social contexts. This study uses a grounded theory design with a qualitative approach that is applied to produce a theory that can explain, at a broad conceptual level, processes, actions, or interactions about substantive topics. Data collection techniques used in this study were documentation studies, participatory observation techniques; autoanamnesis interview technique; and a written assessment using a test tool in the form of the Profile of Nonverbal Sensitivity Test (PONS Test). The stages developed to apply Alpha brain waves in increasing teacher awareness of empathy are, 1) Build and Maintain Rapport; 2) Calibration; 3) Map the Brain; 4) Assertiveness Installation; 5) Drop the Anchor; and 6) Provide Feedback. Through these stages, the teacher's brain waves will be adjusted to Alpha waves, and the problems they have to solve are explored. The results of the analysis show that the proper use of Alpha brain waves can provide benefits in increasing teacher empathy awareness when they manage learning activities in the classroom.